2017
DOI: 10.1021/acs.jpca.7b04808
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Tunneling Predissociations in the 2pπC1Πu±(υ = 19) and 3pπD1Πu±(υ = 4, 5) States of D2 Studied by a Combination of XUV Laser and Velocity Map Imaging

Abstract: The predissociation mechanism of D near the threshold for the production of the D(2s, 2p) fragments has been studied by measuring the fragment yield spectra, fragment velocity map images, and fragment branching ratios D(2s)/(D(2s) + D(2p)) using a combination of XUV laser and velocity map imaging. The predissociation dynamics of the 2pπCΠ(υ = 19) and 3pπDΠ(υ = 4,5) states were studied. The 2pπCΠ(υ = 19) state is a bound state due to a shallow barrier. For the R(0) transition to the 2pπCΠ(υ = 19) state, the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Therefore, higher energy states of the 2pπC state can dissociate via tunneling or coupling with the continuum of the 2pσB state, and both of them correlate to the H­(1s) + H­(2p) channels. The branching ratio measurements showed that the products were indeed mainly of the H­(2p) state . For the predissociation of the 3pπD 1 Π u + state, the angular distribution of the fragments and the channel branching ratio [H­(2p)]/[H­(2p) + H­(2s)] showed that dissociating state has 1 ∑ u + symmetry correlating to H­(1s) + H­(2s), which confirms that the predissociation occurs via the coupling with the vibrational continuum of the 3pσB′ 1 ∑ u + state. …”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Therefore, higher energy states of the 2pπC state can dissociate via tunneling or coupling with the continuum of the 2pσB state, and both of them correlate to the H­(1s) + H­(2p) channels. The branching ratio measurements showed that the products were indeed mainly of the H­(2p) state . For the predissociation of the 3pπD 1 Π u + state, the angular distribution of the fragments and the channel branching ratio [H­(2p)]/[H­(2p) + H­(2s)] showed that dissociating state has 1 ∑ u + symmetry correlating to H­(1s) + H­(2s), which confirms that the predissociation occurs via the coupling with the vibrational continuum of the 3pσB′ 1 ∑ u + state. …”
Section: Introductionmentioning
confidence: 60%
“…Our experimental setup has been described in previous publications, and only a summary is given here. The setup consists of a tunable XUV pump laser (83.19–83.68 nm), a probe laser at 364 nm, and a typical supersonic molecular beam machine equipped with a velocity map imaging component. , The XUV laser was generated by four-wave sum frequency mixing with one fixed frequency laser, one tunable laser, and one pulsed Kr jet as the nonlinear medium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These changes are resulted from the competitions between the direct dissociation channels and the predissociation channels at different positions within the Beutler-Fano profile. For D 2 , very similar ex-perimental measurements have been performed for the 2pπC 1 Π ± u (v=19) and 3pπD 1 Π ± u (v=4, 5) states [20]. Besides the normal electronic predissociation process, tunneling predissociation also plays an important role for the 2pπC 1 Π ± u (v=19) state, especially for the f-parity levels for which tunneling is the only predissociation channel as required by the symmetry.…”
Section: A H 2 (D 2 Hd)mentioning
confidence: 70%